1991
DOI: 10.33584/jnzg.1991.53.2009
|View full text |Cite
|
Sign up to set email alerts
|

Some basic concepts of pasture seed mixtures for New Zealand farms

Abstract: Seeds mixtures for New Zealand pastures developed from British practices with sowing of multi-species seeds mixtures during early years of settlement. Breeding and seed production of ryegrasses and clovers in the 1930s led to use of simple mixtures, still the most commonly used. Since the mid 197Os, new species have been released, and are now becoming more popular. Advantages and some potential problems of species mixtures are outlined, and simple concepts of compiling seeds mixtures are explained, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The ryegrass, which was drilled 6 months after the cocksfoot and tall fescue portions of the mixtures, had lower seedling establishment owing to the competition from the older companion grasses. Generally, seeding rate only influences pasture production in the short term after sowing in single species sowings (Charlton 1991;Harris et al 1973). However, it is seeding rates that farmers have the most influence over and so the expression of the results in terms of the original seeding rates is appropriate in this context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ryegrass, which was drilled 6 months after the cocksfoot and tall fescue portions of the mixtures, had lower seedling establishment owing to the competition from the older companion grasses. Generally, seeding rate only influences pasture production in the short term after sowing in single species sowings (Charlton 1991;Harris et al 1973). However, it is seeding rates that farmers have the most influence over and so the expression of the results in terms of the original seeding rates is appropriate in this context.…”
Section: Discussionmentioning
confidence: 99%
“…The use of pastures sown with several grass and legume species has been a practice long associated with grassland farming (Charlton 1991). The concept is that a balance of pasture species will be reached that produce well under the conditions that prevail in each microclimate across each field.…”
Section: Introductionmentioning
confidence: 99%
“…This study (Table 2) demonstrated that application of fertilizer resulted in a considerable reduction in the size of the germinated grass seed population, but had no measurable effect on the legume or weed. The reason for a reduced size of the germinated grass seed population in the fertilized treatment was probably because the previous (1989–93) history of fertilizer application in the treatment may have restrained the growth of low‐fertility species such as browntop and sweet vernal grass, which produce small but abundant seeds ( Charlton, 1991). This was supported by the finding of Lambert et al .…”
Section: Discussionmentioning
confidence: 99%
“…Grasslands Kara cocksfoot was bred specifically as a grass for dairy pastures (Rumba11 1982). It has therefore been recommended that these species be sown as either single or as mixed grass species swards (Charlton 1992;Moloney 1992) in dairying areas prone to summer dry periods and grass grub damage. Lucerne and conventional insecticides have proven ineffective in combating persistent grass grub and summer dry problems in South Taranaki (Thomson et al 1985), so use of alternative pasture species may be beneficial.…”
mentioning
confidence: 99%